[Site Study "5A"] - P. K. Phillips::::::photographer::: (1970)
A sketch of one of many site studies of a potential, multi-phase "library addition" on Cal Poly's campus. This specific site study is titled "Site Study 5A" and places the addition between Building 1 and Building 52.